Demographic differences in sources of stress in higher educational institutions in Ghana - Ernest Owusu; Chief Bright Akomeah; Francis Duah (Goodwood Publishing, 2021)
Purpose: The current research aimed to investigate demographic differences in job stress prevalence and job stress causes among the staff of universities. Research methodology: The study is based on a descriptive, quantitative, and cross-sectional research design. A sample of 100 respondents, from Sunyani Technical University, were sampled using the convenience sample method. Data were collected in a survey using a questionnaire which was designed by the researchers and administered to the respondents at their workplaces. The collected data were analyzed using descriptive statistics, regression analysis, and One-Way Analysis of Variance. Results were presented in Tables. Results: The findings indicate that significant demographic differences exist in job stress prevalence and job stress causes. The management of universities should take into account the current findings of the research in dealing with job stress. Appropriate policies are recommended to be put in place to deal with stress related to the job to improve staff output, so as not to have a deleterious effect on staff professional work and personal welfare. Limitations: Some respondents felt reluctant to take part in the survey. The causal conclusions cannot be made based on the current findings since a causal investigation was not the focus of the study, and hence was not done. Some respondents also did not answer all the questions asked. Contributions: The paper contributes to the literature in the area of job stress sources and the role demographic factors in job stress causes in higher institutions. The work is the first of its kinds in the study institution on the role of culture and belief on job stress.